Penguatan Ekonomi dan Ketahanan Pangan Masyarakat Melalui Diversifikasi Produk Gula Aren di Desa Sukahurip Kabupaten Ciamis - Purwati Kuswarini Suprapto; Diki Muhamad Chaidir; Dea Diella; Ryan Ardiansyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The palm sugar farmers of Sukahurip Village Ciamis District had difficulty in diversifying their palm sugar into high value and quality products. They felt the need to increase the knowledge and skills of increasing production value and product diversification. Based on the problem, this community service carried out training with the Participatory Rural Appraisal (PRA) approach in which the partners participate in activities carried out in partner locations. The team had succeeded in making a liquid palm sugar formulation that was suitable for use, which previously was the main obstacle experienced by the partners. The results of the focus group discussion (FGD) show that the partners will continue to evaluate the diversification of palm sugar products to maintain the best quality in the hope that they will export the products and become superior to partner villages. The partners will also market the products to a wider community and follow-up from the Ciamis district government and the province.